2018
DOI: 10.1155/2018/9624327
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evaluation of Chromatographic Parameters for Isoquinoline Alkaloids on XB-C18 Core-Shell Column Using Different Mobile Phase Compositions

Abstract: Chelidonium majus L. is a rich source of isoquinoline alkaloids with confirmed anti-inflammatory, choleretic, spasmolytic, antitumor, and antimicrobial activities. However, their chromatographic analysis is difficult because they may exist both in charged and uncharged forms and may result in the irregular peak shape and the decrease in chromatographic system efficacy. In the present work, the separation of main C. majus alkaloids was optimized using a new-generation XB-C18 endcapped core-shell column dedicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Latex is stored in the special secretory cells called laticifers. According to Pharmacopoeial monographs, presence of articulate laticifers with yellowish content is used as an authentication microscopic mark in powdered herb [ 40 , 42 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Latex is stored in the special secretory cells called laticifers. According to Pharmacopoeial monographs, presence of articulate laticifers with yellowish content is used as an authentication microscopic mark in powdered herb [ 40 , 42 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Presence of articulate laticifers with yellowish content is also used as an authentication microscopic mark in powdered herb by pharmacopoeial monographs. The composition of latex is plant organ specific (Tomē and Colombo, 1995 ; Sowa et al, 2018 ). Generally, five groups of alkaloids were found in C. majus .…”
Section: Phytochemistrymentioning
confidence: 99%
“…The presence and number of laticifers is due to the physiological functions of aerial parts and underground parts of the plant, such as responses to environmental factors, defense against herbivory, metabolic reserves, and energy store (Agrawal and Konno, 2009 ). Coptisine [31] was found mostly in fruits and herb (Sārközi et al, 2006 ; Kedzia et al, 2013 ; Sowa et al, 2018 ), whereas berberine [28] showed no significant difference between aerial parts and roots (Tomē and Colombo, 1995 ). Larger amounts of phenanthridine alkaloids like chelidonine [1], chelerythrine [9], sanguinarine [12] were observed in roots rather than in aerial parts of the plants (Tomē and Colombo, 1995 ; Sowa et al, 2018 ).…”
Section: Phytochemistrymentioning
confidence: 99%
“…For example, isoquinoline alkaloids from the roots of Hydrastis canadensis L. were successfully separated with ammonium formate (pH 3.3) and acetonitrile (added with formic acid) as mobile phase [7]. Additionally, several buffer systems that allow for better separation were employed for alkaloid separation in the herbs of Chelidonium majus L., such as acetic acid–ammonium acetate buffer (pH 4) [8] and aqueous solution of ammonium formate adjusted to pH 2.8 [9]. Similarly, formic acid–ammonium acetate buffer solution was utilized to determine alkaloids from the rhizome of Menispermum dauricum DC.…”
Section: Chromatographic Separation Methodsmentioning
confidence: 99%